TRANSCRIPTOME ANALYSIS OF MRNA EXPRESSION PROFILING TO PREDICT POTENTIAL BIOMARKERS INDUCED IN BREAST CANCER-BRCA1 - J, Reshma Jacob (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Breast cancer is most common cancer type to women with 5, 00,000 deaths in every year worldwide. The purpose of the present study is to predict the somatic variants and copy number variants present in BRCA1 genes using 6 paired samples of the glandular tissues. Methods: In this context DNA sequencing technology is advanced method used to identify biomarkers that helps patients to have treatment. Results: From whole genome sequence several gene mutations are predicted using Annovar and snpEff tools from GATK tool kit and classified only non-synonymous SNVs from all datasets and predicted the 28 novel genes that significantly associated with breast cancer. Conclusion: Results are classified with both breast cells and breast cancer cells, identified 13 genes which are most commonly expressed and is further used for molecular diagnostics.